3D scanning probe nanotomography of tissue spheroid fibroblasts interacting with electrospun polyurethane scaffold - A. E. Efimov; O. I. Agapova; L. A. Safonova; M. M. Bobrova; V. A. Parfenov; E. V. Koudan; F. D. A. S. Pereira; E. A. Bulanova; V. A. Mironov; I. I. Agapov (eXPRESS Polymer Letters, 2019)
We present a 3D study of nanostructural features of a bioprinted tissue spheroid interacting with polyurethane dual-scale biocompatible scaffold manufactured by three-dimensional printing and electrospinning. Three-dimensional analysis of fibroblasts interacting with electrospun polyurethane fibers was conducted using scanning probe nanotomography with an experimental setup combining ultramicrotome and a scanning probe microscope. Three-dimensional reconstruction demonstrates direct visualization of cell membrane protrusions and coherent cell-fiber interfaces, the formation of which is a prerequisite for an efficient tissue engineered implant. Analysis of obtained 3D data allows for quantitative calculation of the important morphological parameters of adhered cells, scaffolds, and cell-scaffold interfaces. The proposed method may be successfully applied to investigate 3D cell-scaffold constructs at nanoscale.